Continuity or Discontinuity – the Case of Macedonian Phonetics - Irena Sawicka (Colloquia Humanistica, 2015)
Continuity or Discontinuity – the Case of Macedonian Phonetics The article presents its principal topic of the continuity of linguistic phenomena based on the material of Macedonian phonetics, treated as a constituent of south-east European phonetics, and not as an element of the Slavic world. It provides, firstly, a static perspective, produced by enumerating typologically relevant features. Seen from this perspective, Macedonian phonetics is a component of the Central Balkanic area. Secondly, emphasis has been put on processes of phonetic convergence and their differences from those of grammatical convergence. These difference account for the instability of phonetic features, or in any case their generally lesser stability compared to morphosyntactic features, but on the other hand also for the possibility for some phenomena to survive in small areas, in a few dialects, and the possibility for linguistic features to reappear, which stems from alternating cross-dialectal interference. The Macedonian language territory abounds in such situations due to its multi-ethnicity, which is greater here than anywhere else in the Balkans. Particular in this respect is the area of Aegean Macedonia, where Slavic dialects are “protected” from the influence of the literary norm – albeit in the case of Macedonian even the realisation of the literary norm is not entirely stable in terms of phonetics.